Serum Omentin Levels in Asthma Patients - Kalayci, Defne; Konuk, Suat; Tug, Tuncer (Archives of Clinical and Biomedical Research, 2018)
Objective: Asthma is a heterogeneous disease characterized by chronic airway inflammation. We aimed to determine the serum levels of omentin in asthma patients and its relation to atopy. Methods: A total of 47 asthmatic patients and 39 healthy adults were involved. In addition to routine biochemical tests, the serum omentin levels were determined by the ELISA method. The Statistical evaluation was performed using the SPSS 16.0 package program and p <0.05 values were considered significant. Results: Serum omentin levels of asthmatic patients (107.0 ± 23.7 pg /ml) were higher than the control group (84.0 ± 44.2) (p = 0.028). A statistically significant difference was found according to the severity of asthma (p=0.008). Serum omentin levels were significantly higher in the mild persistent asthma group compared to the moderate asthma group (p = 0.021). In the control group, omentin levels in the non-smokers were significantly higher than the control group (p = 0.005). In the control group, the serum omentin levels of the women were significantly higher than the levels in men (p <0.001). In asthma group, there was a negative correlation between omentin level and the body mass index in men (p= 0.040, r= -0.599). In the control group, the same negative correlation was detected between omentin level and the body mass index in women (p=0.008, r= -0.484). Conclusion: Serum omentum levels were found to increase in asthmatic patients. In addition, it has been shown that omentum levels are higher in women than men.